2016
DOI: 10.3109/15563650.2016.1146740
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis and comparison of caffeine administered rapidly or slowly in coffee chilled or hot versus chilled energy drink in healthy young adults

Abstract: Context: There is a paucity of data describing the impact of type of beverage (coffee versus energy drink), different rates of consumption and different temperature of beverages on the pharmacokinetic disposition of caffeine. Additionally, there is concern that inordinately high levels of caffeine may result from the rapid consumption of cold energy drinks. Objective: The objective of this study was to compare the pharmacokinetics of caffeine under various drink temperature, rate of consumption and vehicle (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 11 publications
7
65
1
1
Order By: Relevance
“…As observed in other studies the disposition of caffeine was different between male and female subjects ( Table 2) with female subjects having a higher C max and AUC compared to males, but there was no difference in these parameters after normalizing for the subjects' body weight. A previous study reported similar results though a significant difference between males and females in the C max and AUC was maintained even after normalized for body weight [15]. The primary metabolic pathway of caffeine is conversion to paraxanthine by CYP1A2, and lower CYP1A2 activity in women vs. men has been reported in Caucasian, African-American and Chinese subjects [16], which would be consistent with greater systemic exposure to caffeine in females given an equivalent dose as males.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As observed in other studies the disposition of caffeine was different between male and female subjects ( Table 2) with female subjects having a higher C max and AUC compared to males, but there was no difference in these parameters after normalizing for the subjects' body weight. A previous study reported similar results though a significant difference between males and females in the C max and AUC was maintained even after normalized for body weight [15]. The primary metabolic pathway of caffeine is conversion to paraxanthine by CYP1A2, and lower CYP1A2 activity in women vs. men has been reported in Caucasian, African-American and Chinese subjects [16], which would be consistent with greater systemic exposure to caffeine in females given an equivalent dose as males.…”
Section: Discussionsupporting
confidence: 71%
“…Our data do not provide support for this inference as the mean T max value after administration of the gum was longer than the value we found for the energy drink, a finding that is also further supported by the shorter T max values that have been recently reported by White et al . for caffeine administered in the form of an energy drink and hot coffee . A comparison of caffeine disposition after administration by capsule, gum, coffee, energy drink and AeroShot in Table demonstrates the similarity in caffeine disposition irrespective of the dosage form, with the only differences being the T max , which is energy drink = coffee < gum < AeroShot < capsule.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, considering that a fraction of ca . 1–4 % of PAR and CAF are excreted in urine in their unchanged form and that the dosages administered usually are on the range of hundreds of milligrams several times per day, the system proposed here can surely be employed for the monitoring of the levels of these compounds in patients aiming to avoid and detect overdoses . The proposed approach showed satisfactory sensitivity and selectivity besides simplicity and reduced consumption of samples and reagents, which leads to lower waste generation and makes it compatible with the concepts of green chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…23 Similarly, in a study by Krieger et al using a 200-mg dose, there were no significant differences in absorption between the natural and synthetic caffeine sources. 22 Caffeine concentration reached its peak plasma concentration for both sources on average between 63 and 75 minutes postingestion, which is consistent with other studies of oral doses of caffeine varying from 160 to 200 mg. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Caffeine was analyzed using the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. [25][26][27] All laboratory analysis was conducted by Keystone Bioanalytical, Inc (North Wales, Pennsylvania: https://www.keystonebioanalytical.com/), a licensed contract analytical laboratory. Keystone Bioanalytical Inc. developed a method, M161202, for the quantification of several caffeoylquinic acids (listed below) in K 2 -ethylenediaminetetraacetic acid (EDTA) human plasma using LC-MS/MS.…”
Section: Chlorogenic Acids and Caffeine Analysismentioning
confidence: 99%